Análise da viabilidade técnica dos levantamentos de baixo custo de perfil e irregularidade longitudinal de pavimento com o uso de acelerômetros controlados por arduino auxiliado por bicicleta - Ramos, Saulo Passos (2017)
User safety and rolling comfort are functional parameters that can be evaluated, among other criteria, by roughness . Given that there is a strong relation between the profile and the longitudinal irregularities of a pavement, this affinity allows to analyze the evolution of that parameter. In order to carry out the survey of a longitudinal profile of a pavement and the evaluation of roughness , according to the current norms, we can mention, respectively, the level and sighting methods and the laser profilometer. The first one demands a lot of time and physical effort from the operators and the second, a lot of financial resources, since it is a n equipment that costs almost R $ 400,000 ,00 . Thus, it is reasonable to analyze the feasibility of the use of new technologies in order to reconstruct a trajectory related to the longitudinal profile of a pavement and to evaluate an d monitor the evolution of roughness in a practical and economical way. One of the ways to obtain the profile and to evaluate the roughness in this work was the use of inertial sensors, such as an accelerometer. This sensor controlled by an a rduino microco ntroller provides acceleration data, which, after processing the data using the Matlab, Excel, Proval and Minitab software, sought to verify the quality and behavior of the measured signals in order to evaluate the capacity Of the sensor to reconstruct the longitudinal profile and the potential of the equipment to evaluate the longitudinal irregularities of a pavement. In the data collection stage, a Scottish fork and an air rail trolley were used in the laboratory, and a bicycle, with which several passes were made in an experimental section located in the Pici Campus of the Federal University of Ceará. The acceleration data obtained by the accelerometer were processed through digital signal filters and correlated with the International Roughness Index (IRI ) values. By the analysis of the results, it was possible to conclude that the equipment is not efficient to obtain the longitudinal profile of a pavement, due to the low speed of the bicycle. However, the accelerometer controlled by arduino had a high pot ential to evaluate the roughness of a pavement, with 85% of satisfactory results.